Respondent-Driven Sampling With Youth Who Use Drugs: A Mixed Methods Assessment. (December 2019) - Selfridge, Marion; Card, Kiffer G.; Greer, Alissa; Ferencz, Sarah; Lachowsky, Nathan; Macdonald, Scott
Respondent-driven sampling (RDS) has been widely used for recruiting hard-to-sample populations, particularly men who have sex with men and people who inject drugs from large urban centers. The aim of this article was to examine the feasibility of using RDS among nonmetropolitan youth who use drugs. Between May 2017 and June 2018, RDS was used to recruit youth who use drugs, ages 16–30, in three nonmetropolitan Canadian cities. All participants completed a 1-hr interviewer-administered survey. Youth received 25 for the interview, up to five coupons to recruit peers and 5 per coupon returned. Crude and RDS-weighted descriptive statistics were produced using RDS-II weights as were homophily (the tendency for people to be similar) and network size estimates. Statistically significant differences between seeds and recruits were identified using logistic regression. A subsample of recruits participated in qualitative interviews ( n = 38). Data from these interviews were inductively analyzed to identify barriers that could be used to explain the challenges with chain-referral recruitment among this population. In total, 449 youth were recruited. Due to unproductive chains, 57.2% ( n = 257) of the sample was comprised of seeds and 322 (72%) did not have a single coupon returned. Barriers to recruiting other youth included logistical challenges, fear of police, concerns about confidentiality, stigma of substance use, and poor financial incentive. Our study shows that RDS can be used to reach younger participants but also highlights the need for formative research and flexibility in recruitment to help mitigate unsuccessful RDS among nonmetropolitan youth who use drugs.